Ruju’ dan Problematikanya dalam Perspektif Islam - Nurcahaya Nurcahaya (Al-Ulum: Jurnal Pendidikan Islam, 2021)
This study aims to analyze ruju' in an Islamic perspective. The research method used is qualitative with a library research approach. The results of the study indicate that the basic law of reconciliation is permissible but the law of reconciliation becomes unlawful when the husband refers to his wife with the aim of causing trouble and harm to his wife. And it becomes makruh if the husband sees that he will not be able to enforce Allah's boundaries in the household if he refers his wife again. Among the wisdom of reconciliation is to restore the integrity of the household, improve the relationship between husband and wife and their offspring and provide the opportunity to be together again as a form of God's grace and love for husband and wife, and is God's favor to them so that they can find happiness.Keywords: Ruju’, Hukum Islam, Ushul Fikih